ANALYSIS OF FLUID FLOW BEHAVIOR IN THE FRACTURED RESERVOIRS: REVIEW PAPER - Mustafa M. Alobaidy; Abdul Rahim Risal (International Journal of Innovations in Engineering Research and Technology, 2022)
The naturally fractured reservoirs are considered complex reservoirs in the petroleum industries where the engineers face some difficulties in the modeling of naturally fractured reservoirs. The main problem of fractures is the tectonic movements of fractures which affect the hydrocarbons flow during transportation from matrix to fracture, and drilling and productions processes. This review paper presented some previous about hydrocarbons leakage, drilling and production damages, and modeling issues which caused a loss of hydrocarbons in the naturally fractured reservoirs. The purpose of this review paper is to analyze the hydrocarbons flow behavior during production processes even to reach the perfect model in this study. This review paper depended a lot on Warren and Root’s theory and extended by using new parameters and assumptions. This study got on perfect results to analyze hydrocarbons flow. This review paper is shown that the difference in the properties of natural fractures affected the flow of hydrocarbons during the transition from the matrix to the fractures, which affected drilling operations and hydrocarbon production. In addition, dual-porosity affected the movement of the fluid. Dual porosity resulted in fractures and or dissolving that produces holes in the reservoir.